On one method of factorization of polynomials - Dzhalladova, I. A. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We propose and justify a numerical method of factorization of polynomials with complex coefficients. We construct and algorithm of factorization of polynomials with real coefficients into real factors in the case of multiple roots.